The Role of Ria Miranda in Improving the Implementation of the Ramadan Campaign Towards Giordano Product Sales - Sarahnisa, Nabila; Hidayat, Rahmat; Kusworo, Ahmad Dzulfikri Budi (Journal of Advances in Accounting, Economics, and Management, 2024)
This research discusses the role of Ria Miranda in improving the implementation of the Ramadan Campaign towards Giordano product sales. With the development of time and changes in societal behavior, Giordano collaborates with local designers with the aim of boosting product sales. This involves determining materials and ornaments that form the basis of the theme chosen for the campaign. This study also examines the marketing strategies employed by both brands, such as conducting product launching events, optimizing public figures as promotional mediums to foster positive interaction towards purchase intention. Collaborative strategies between brands to enhance campaign execution are considered to be relatively easy and effective in their application, thus influencing sales increase.